Inter-varietal variation in the composition, physicochemical properties and antioxidant activity of winter melon [Benincasa hispida (Thunb.) Cogn.] fruit seeds and seed oils - Mohammad, Nor Azizah (2015)
The proximate composition of seeds and the physicochemical properties and antioxidant activity of extracted seed oils from two Malaysian winter melon cultivars namely round (Cultivar 1) and hybrid (Cultivar 2) were examined. The seeds from Cultivar 1 and Cultivar 2 exhibited protein, total dietary fiber, carbohydrate, moisture and ash contents 18.26-20.45, 41.55-46.30, 1.70-5.78, 6.47-7.03, and 3.73-7.42%, respectively. The oils were extracted based on Soxhlet method by petroleum ether, whilst yields ranged from 17.78-23.55% (wt/wt). The extracted oils were analyzed for physicochemical parameters, fatty acids, tocopherols profiles, phenolic compound, and antioxidant activities. The physicochemical properties showed ranges for specific gravity (25°C), refractive index (nD 25°C), iodine value (IV), saponification value (SV), peroxide value (PV), and free fatty acid (% as oleic acid) as 0.88-0.91, 1.4627- 1.4630, 119.9-125.1 g I/100 g oil, 182.3-194.1 mg KOH/ g oil, 1.13-1.27 mequiv.O2/kg, and 1.57-1.87%, respectively. The oil color intensity in terms of yellow and red units was 6.9Y + 1.0 R to 8.9Y + 1.9R. Linoleic acid (C18:2) was established to be the principal fatty acid (63.10-70.64%) followed by C16:0 (12.45-17.59%), C18:1 (8.46-12.73%) and C18:0 (5.13-6.26%). The predominant tocopherols were β- tocopherol, followed by γ-tocopherol, δ-tocopherol, γ-tocotrienol, and α-tocopherol, respectively. Vanillin was the principal compound in both seed oils ranging from 38.9 to 51.4% of the total phenolic compound (12.27-17.25 μg/g), including gallic acid, protocatechuic acid, 3,4-dihydroxybenzaldehyde, vanillic acid, para-coumaric acid, trans-cinnamic acid and ferulic acid. Three solvent systems namely ethanol, methanol, and isopropanol at two different concentrations (80% and 100%) were used as extraction solvents for assessment of antioxidant activity and total phenolics content (TPC) of the oils. The results revealed the notable effect of extraction solvents. TPC of oil extracts were ranged from 19.37 to 203.93 μg GAE/g oil. The highest trolox equivalent antioxidant capacity (TEAC) among oil extracts was found to be not significant between two cultivars. Most of oil extracts from Cultivar 2 showed significantly higher TPC and antioxidant activity in terms of IC50 value (DPPH radical), compared to Cultivar 1. The data of this study support that winter melon seed oils of the tested cultivars could be a dietary source of tocochromanol, phenolic compound, and natural antioxidants.